Sosialisasi Perlindungan Hak Remaja Dalam Kasus Cyberbullying di Lingkungan Remaja SMKN 1 Kemlagi Kabupaten Mojokerto - Diah Cahyani; Muhammad Yudi Hadianto; Andika Fadila Pratama Yuda; Agus Nur Wijaya; Bella Putra Madya; Dika Lutfi Al Khod’ri; Aisyah Putri Mulyanto; Chamelia Nur Abdillah; Andry Prasetya Gunawan; Berliana Kartika Sari; Ayunda Nurul Safitri; Indra Liliana; Siti Muamalah Ika Nur Marifa; Anas Sobirin; Avrila Rahmadhani Apriandita; Pramudyah Wiji Masruroh; Andrian Lukman; Yuniar Rahma Sacta; Dian Novita Emiliyanti; Muhammad Luis Armando; Dewi Putri Anjani (Jurnal Pengabdian Masyarakat Sains dan Teknologi, 2025)
This research aims to explore the protection of teenagers' rights in dealing with cyberbullying among students at Kemlagi State Vocational School, Mojokerto Regency. In the digital era, the use of social media among teenagers is increasing, but this also brings challenges in the form of cyberbullying, which can have a negative impact on their mental and emotional health. This research uses an outreach method which includes lectures, conveying the impact of cyberbullying, and explaining the rights of teenagers. This activity was held on December 12, 2024, involving students, teachers and students of Mayjen Sungkono University. Initial observation results show students' minimal knowledge about cyberbullying and their rights. Through socialization, students are expected to understand the consequences of cyberbullying, as well as their rights to be protected. Evaluation is carried out through questionnaires to measure student understanding after the socialization is carried out. It is hoped that this research can provide recommendations for schools, parents and the community in dealing with cyberbullying problems effectively, as well as increasing awareness of the importance of protecting teenagers' rights in cyberspace.